2016
DOI: 10.5194/nhess-16-1979-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the search and rescue LEEWAY model in the Tyrrhenian Sea: a new point of view

Abstract: Abstract. The trajectories' prediction of floating objects above the sea surface represents an important task in search and rescue (SAR) operations. In this paper we show how it is possible to estimate the most probable search area by means of a stochastic model, schematizing the shape of the object appropriately and evaluating the forces acting on it. The LEEWAY model,a Monte Carlo-based ensemble trajectory model, has been used; here, both statistical law to calculate the leeway and an almost deterministic la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…These results show that TRAPs may be completely hidden in instantaneous streamline and horizontal divergence plots, yet predict the shortterm fate of passive tracers, as well as inertial objects influenced by windage, such as drifters. Although incorporating inertial, windage, and leeway effects could, in principle, provide a better prediction, in a SAR operation the inertia of the target objects is generally unknown 14 and wind information is unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that TRAPs may be completely hidden in instantaneous streamline and horizontal divergence plots, yet predict the shortterm fate of passive tracers, as well as inertial objects influenced by windage, such as drifters. Although incorporating inertial, windage, and leeway effects could, in principle, provide a better prediction, in a SAR operation the inertia of the target objects is generally unknown 14 and wind information is unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the search areas may be more complex than just an ellipse; it may well be a set of disjoint areas, each one with an associated different POC (e.g. Abi-Zeid and Frost, 2005;Breivik and Allen, 2008;Guitouni and Masri, 2014;Di Maio et al, 2016). Figure 17 shows the evolution of the ellipse areas, averaged over all IABP buoys.…”
Section: Predictive Skills Of Nextsim and Of The Fd Modelsmentioning
confidence: 99%
“…New advancements in leeway calculation have shown that it is possible to create a model of leeway drift using the balance of hydrodynamic and aerodynamic forces. This was conducted by Di Maio et al (2016) on a person in the water, with the modeled leeway performing better than the statistical approach described above. If this model proves accurate with other objects, it could reduce the need for direct measurement of leeway parameters.…”
Section: Search and Rescue Fundamentalsmentioning
confidence: 99%